2003
DOI: 10.1074/jbc.m210288200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Pyruvate Kinases from the Hyperthermophilic Archaea Archaeoglobus fulgidus, Aeropyrum pernix, and Pyrobaculum aerophilum and the Hyperthermophilic Bacterium Thermotoga maritima

Abstract: Pyruvate kinases (PK, EC 2.7.1.40) from three hyperthermophilic archaea (Archaeoglobus fulgidus strain 7324, Aeropyrum pernix, and Pyrobaculum aerophilum) and from the hyperthermophilic bacterium Thermotoga maritima were compared with respect to their thermophilic, kinetic, and regulatory properties. PKs from the archaea are 200-kDa homotetramers composed of 50-kDa subunits. The enzymes required divalent cations, Mg 2؉ and Mn 2؉ being most effective, but were independent of K ؉ . Temperature optima for activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 37 publications
2
61
0
Order By: Relevance
“…acidophilum enzyme, archaeal PKs do not depend on the presence of monovalent cations like K ϩ or NH 4 ϩ , as described for many other PKs from Bacteria and Eukarya. This independence was attributed to the substitution of a conserved glutamate, which is highly conserved in the K ϩ sites of PKs stimulated by monovalent cations (232,236). This glutamate is also present in the K ϩ -dependent Tpl.…”
Section: Phosphoenolpyruvate Conversion To Pyruvatementioning
confidence: 99%
See 4 more Smart Citations
“…acidophilum enzyme, archaeal PKs do not depend on the presence of monovalent cations like K ϩ or NH 4 ϩ , as described for many other PKs from Bacteria and Eukarya. This independence was attributed to the substitution of a conserved glutamate, which is highly conserved in the K ϩ sites of PKs stimulated by monovalent cations (232,236). This glutamate is also present in the K ϩ -dependent Tpl.…”
Section: Phosphoenolpyruvate Conversion To Pyruvatementioning
confidence: 99%
“…From phylogenetic analyses, it has been concluded that the PK family is subdivided into two distinct branches (232,235,236), and it appears that this clustering is due to K ϩ dependence or independence (236). The archaeal PK sequences show a high degree of similarity with their bacterial and eukaryotic counterparts, including the prosite consensus patterns for PKs (232,235). PKs, as deduced from the crystal structures available from bacterial and eukaryotic sources and also recently from the crenarchaeon Pyb.…”
Section: Phosphoenolpyruvate Conversion To Pyruvatementioning
confidence: 99%
See 3 more Smart Citations